Reappraising political theory revisionist studies in the history of political thought - Ball, Terence; Oxford eBooks (Oxford : Clarendon, 1995)
Ball begins by setting out his liberating view of the way we should approach 'classic' texts. He offers new readings - and reappraisals - of key authors and classic works in political theory, arguing that the importance of the great texts lies in their repeated reinterpretation in the light of problems that arise for present-day readers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political science -- History; Political science -- Philosophy; Electronic books